Achieving Pseudo‐Ductile Behavior of Carbon Fiber Reinforced Polymer Composites via Interfacial Engineering. Issue 2 (28th September 2020) - Szebényi, Gábor; Magyar, Balázs; Czigany, Tibor
Abstract : This article presents an investigation of the properties of interfacial engineered carbon fiber (CF) reinforced polymer (CFRP) composites. Poly(ϵ‐caprolactone) (PCL) is used as an interface engineering/interlayer material to modify the interfacial shear strength (IFSS) between the phases, with which it is aimed to increase the pseudo‐ductility of CFRPs. A stable crack propagation behavior can be achieved through interfacial engineering due to the locally weakened connection between the resin and the fiber reinforcement. Various grid patterns of PCL interfacial additive are designed, and 3D printed on the unidirectional (UD) CF (UDCF) surfaces by fused deposition modeling (FDM) and the UDCF is infiltrated with an amine‐cured epoxy (EP). The resulting composites are subjected to mechanical tests. In each case, the PCL‐rich interphase increases ductile pseudo‐behavior, and the type of grid affects the mechanical response. Abstract : The article presents results from the research aimed at composites showing pseudo‐ductile behavior. The approach is novel; different 3D printed grids are used (poly(ε‐caprolactone) (PCL), which is soluble in the epoxy matrix) placed at the fiber‐matrix interface to modify surface adhesion and thereby convert the failure mode of composite structures from instant catastrophic to elongated ductile fracture.